Pengaruh minat belajar dan berpikir kritis terahadap literasi numerasi peserta didik kelas V SD se-Kecamatan Laweyan - Septia, Aulia Yogi; Rukayah, Rukayah; Ardiansyah, Roy (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
This study aims to find out: 1) the effect of learning interest on the numeracy literacy skills of fifth grade elementary school students 2) the effect of critical thinking skills on the fifth grade elementary school students' numeracy literacy skills, 3) the effect of learning interest and critical thinking skills on the numeracy literacy of fifth grade elementary school students. The research method used is a quantitative research method with an associative research design. The population of this study were all fifth grade elementary school students in Laweyan District with a sample of 53 fifth grade elementary school students. The results obtained in this study are: (1) there is a positive influence between learning interest on the numeracy literacy skills of fifth grade elementary school students in Laweyan District with a large influence of 23.1%, (2) there is a positive influence between thinking skills critical of the numeracy literacy ability of fifth grade elementary school students in Laweyan District with a large influence of 23.8%, (3) there is a positive influence between learning interest and critical thinking ability together on the digital literacy ability of fifth grade elementary school students throughout Laweyan District with a large influence of 29.9%.